Phenotypic variation of south-western Atlantic clam Mactra isabelleana (Bivalvia: Mactridae) - Signorelli, Javier Hernan (2012)
The phenotypic shell shape variation of Mactra isabelleana was tested using the geometric morphometric method. Four localities were sampled along the Río de la Plata estuary and the coast of Buenos Aires province. Principal component analysis and canonical variates analysis of the first principal components were performed to reveal the shell variation and differences among localities, respectively. The specimens from different microhabitats mostly overlapped, although differences in shape were observed in the development of the umbo, the enlargement of the dorsoventral axes and the elongation of the posterior end. The ecological and physical parameters that could influence shell shape variation are discussed.